Familias disfuncionales y su incidencia en el estado emocional de los estudiantes del cuarto, quinto y sexto año de centro de educación básica unión nacional de educadores de la ciudad de Machala, periodo lectivo 2013-2014 - Córdova Contreras, Cristina Piedad (2014)
The family meets: very important functions first social institution, it houses within it almost exclusively, or at least most of the time, in the early years, future citizens who are modeled Alli Physically and morally. So the family is the first trainer of Children and consequently f healthy adults.